Exploring drug-surfactant interactions and their impact on the intrinsic surface properties of aqueous dissolution media - Phoebe Greensides; Mark McAllister; Inese Sarcevica; Irena Tomaszewska (University of Huddersfield Press, 2022)
Surfactants are often used to improve the solubility of a compound for dissolution studies in aqueous media. Having observed non-linear solubility enhancement with increasing surfactant concentration, this study investigated the effect of a poorly soluble, zwitterionic, moderately lipophilic drug, Compound A, on the critical micelle concentration (CMC)of sodium lauryl sulfate (SLS) in phosphate buffer. A force tensiometer was used to measure the surface tension of the solutions over a range of surfactant concentrations. The presence of Compound A demonstrated a decrease in the CMC, suggesting that the solution favours micellisation at lower surfactant concentrations in the presence of the drug. Future studies will use a fully saturated solution of Compound A to explore this observation further. Additional experiments will also investigate micelle formation of SLS with other compounds.